Early detection of MDR Mycobacterium tuberculosis mutations in Pakistan - Ayma Aftab (Nature Portfolio, 2021)
Abstract The result of improper treatment has led to the rise of Multidrug-resistant (MDR) strains. This concern still exists in Pakistan. In order to save energy, time and resources an early detection of resistant cases is imperative. Thus, a treated group of 100 isolates and a control group of 56 untreated isolates were studied. PCR and gene sequencing showed mutations at codon 531 and 513 in the rpoB gene. 12% of cases showed a double mutation in the rpoB gene. katG gene showed mutations at codon 315 and 299. 28.6% of the control group cases were positive for MDR whereas 100% of the treated group were positive for MDR. This study explores the significantly increasing ratio of MDR-TB among Pakistani population. This study provides prevalent MDR mutations among Pakistanis and suggests developing such molecular assays that are time and cost effective. Importance: Pakistan is a developing country and has fourth highest incidence rate of MDR-TB. The treatment of MDR-TB is the use of second line drugs that has severe side effects as well as it requires long time span. One of the strategies to control the spread of MDR-TB is to decipher the aberrations at molecular level in order to formulate potent drugs that can treat the patients within short span of time. Determining the mutation profile of MDR in Pakistani populations will open new horizons for the improvement of drug treatment regimens to make it more effective or for the development of novel potent drugs and vaccines to better treat the drug-resistant TB. Moreover, this study will be help in disease control program.